TP53-mutated MDS and AML: immune dysregulation, tumor microenvironment, and emerging therapeutic strategies - Albakri, Marwah M. (Frontiers in Oncology, 2025)
TP53 mutations drive oncogenesis and therapeutic resistance in myelodysplastic syndromes (MDSs) and acute myeloid leukemia (AML), impairing p53-regulated functions such as apoptosis, immune surveillance, and genomic stability, leading to immune evasion and metabolic reprogramming. The tumor microenvironment in TP53-mutated MDS and AML fosters leukemic progression through cytokine dysregulation, altered metabolism, and immune suppression. Current therapies, including chemotherapy and hypomethylating agents, offer limited efficacy, resulting in poor overall survival rates for these high-risk patients. However, novel therapeutic approaches provide promising avenues, including MDM2 inhibitors, p53-reactivating agents, pathway-targeted inhibitors (Hedgehog, Wnt, NF-κB), immune modulation (checkpoint inhibitors, CAR-T therapy), metabolic interventions (fatty acid metabolism, glycolysis), and gene-editing technologies (CRISPR/Cas9, base editing). This review explores the mechanisms of immune dysfunction in TP53-mutated MDS and AML while highlighting emerging therapeutic strategies, emphasizing the integration of targeted, metabolic, and immune-modulating therapies as a transformative approach to improve patient outcomes.